Crystal structure of 3,5–di-O-benzoyl-1,2-O-isopropylidene-α–D-ribose, C22H22O7 - Wu Binbin; Chen Guangying; Ding Haixin (Zeitschrift für Kristallographie - New Crystal Structures)
C22H22O7, orthorhombic, C2221 (no. 20), a = 8.891(2) Å, b = 17.938(5) Å, c = 25.996(6) Å, V = 4146.0(18) Å3, Z = 8, R gt(F) = 0.0461, wR ref(F 2) = 0.1189, T = 296 K.